2019
DOI: 10.1097/mej.0000000000000512
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the National Institute for Health and Clinical Excellence Head Injury 2014 Guidelines in a major children’s hospital emergency department

Abstract: The implementation at the Sheffield's Children NHS Foundation Trust was successful in satisfying the aim of CG176 by increasing adherence and decreasing CT head scans. This success could be explained by the formal implementation to the new cohort of doctors and better physician agreement with the guidelines. The increase in adherence is contrary to the previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Stiell et al received similar answers regarding ED overcrowding that required more expedient care, possibly favouring a quicker but not entirely guideline-adherent approach [ 8 ]. An implementation study for the National Institute for Health and Care Excellence 2014 head injury guidelines showed a higher than expected percentage of early discharges from the ED, and the authors speculated that this could, at least partly, be attributed to ED overcrowding [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stiell et al received similar answers regarding ED overcrowding that required more expedient care, possibly favouring a quicker but not entirely guideline-adherent approach [ 8 ]. An implementation study for the National Institute for Health and Care Excellence 2014 head injury guidelines showed a higher than expected percentage of early discharges from the ED, and the authors speculated that this could, at least partly, be attributed to ED overcrowding [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of guidelines in the work environment as a reminder of their existence and their intrinsic characteristics is also a factor that previous studies have either shown or speculated as actually or potentially beneficial to increase use. A workplace culture that emphasises guideline adherence through colleague encouragement and endorsement from the department management can also increase guideline adherence [ 17 19 ].…”
Section: Discussionmentioning
confidence: 99%